By parallel reasoning the construction and evaluation of analogical arguments - Bartha, Paul F. A., 1964- (New York ; Oxford : Oxford University Press, 2010)
In this work, Paul Bartha proposes a normative theory of analogical arguments and raises questions and proposes answers regarding the criteria for evaluating analogical arguments, the philosophical justification for analogical reasoning, and the place of scientific analogies in the context of theoretical confirmation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Analogy; Reasoning